(How) Can Recent Cognitive Studies Contribute to Literary Interpretation? - Locatelli, Angela (Armenian Folia Anglistika, 2020)
This essay wishes to engage with the crucial issue of the interpretation of literary texts from the specific perspective of the rise of Cognitive Sciences in the past two or three decades. One of the stimulating, but also controversial elements of Cognitive Literary Studies is the variety of denominations of the field itself. Different labels have been adopted to define it, including: “Cognitive Poetics”, “Cognitive Semiotics”, “Cognitive Stylistics”, “Cognitive Literary Studies”, “Cognitive Criticism”, and “Cognitive Literary Science”. A crucial problem that has variously been dealt with but that still remains open to discussion (and has sometimes promoted a questioning of the usefulness of the neurosciences in the interpretation of literary works), is the problem of the affordances of a cognitive approach to the specificity of literary artifacts. This contribution will therefore address and investigate this timely topic and illustrate aspects of the dynamics of literary interpretation that the cognitive sciences have recently productively developed. In particular, it will focus on the following elements: various perspectives in “the neurohumanities”, “literariness and the brain”, “the respective contribution of the cognitive sciences and of literature to the knowledge of the human mind”.